IMPROVING THE ASSESSMENT SYSTEM IN DISTANCE EDUCATION (Ustozlar uchun, 2025)
The Distance Education scenario has seen a sudden boom in far-reaching changes in traditional modes of education and has raised assessment as a most pressing issue in online education systems. Assessment in a wholesome way has become a sine qua non in institutions today as it ensures assessment in education coupled with a measure of progress in a positive way in all modes of education systems today. This paper discusses challenges in assessing learners in distance education and introduces novel solutions in improving assessment systems in distance education modes. A major emphasis has been placed in this paper upon issues related to assessment systems in distance education modes based upon innovative solutions related to assessment systems in distance education modes based upon innovative solutions regarding Formative Assessment and Technology in Distance Education modes today.